2022
DOI: 10.3390/ijerph19074093
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Estimation of 4-Cumylphenol, 4-t-Octylphenol, Nonylphenol, and Volatile Leachate Phenol Degradation by the Microscopic Fungus Umbelopsis isabellina Using a Battery of Biotests

Abstract: The phenolic xenobiotics nonylphenol (NP), 4-tert-octylphenol (4-t-OP), and 4-cumylphenol (4-CP) have the potential to seriously disrupt the endocrine system. Volatile phenols (VPs), especially those present in landfill leachate, also adversely affect the health of numerous organisms. Microbial degradation of xenobiotics can result in the formation of intermediates with higher toxicity than the precursor substrates. Therefore, the main aim of this study was to assess the changes in environmental ecotoxicity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…For example, the ascomycetous fungus Myrothecium roridum IM 6482 has been shown to have a high potential to eliminate bisphenol A (BPA) [ 60 ] and textile dyes [ 61 ]. Janicki et al [ 62 ] described that the filamentous fungus Umbelopsis isabellina IM 833 adapted to LL and degraded nonylphenol, 4- tert -octylphenol, 4-cumylphenol, and volatile phenols to less-toxic intermediates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ascomycetous fungus Myrothecium roridum IM 6482 has been shown to have a high potential to eliminate bisphenol A (BPA) [ 60 ] and textile dyes [ 61 ]. Janicki et al [ 62 ] described that the filamentous fungus Umbelopsis isabellina IM 833 adapted to LL and degraded nonylphenol, 4- tert -octylphenol, 4-cumylphenol, and volatile phenols to less-toxic intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…A BOD 5 /COD ratio less than 0.2 means that the wastewater is practically nonbiodegradable, while values in the range of 0.5–0.7 indicate that the wastewater can be easily biodegraded. In the study by Janicki et al [ 62 ], the BOD 5 /COD ratio was 0.86, indicating that the leachate was readily biodegradable. LL also contains inorganic contaminants and petroleum hydrocarbons, which the fungus is known to be as a source of carbon and energy.…”
Section: Resultsmentioning
confidence: 99%
“…Parabens mainly include methylparaben (MeP), ethylparaben (EtP), propylparaben (PrP), butylparaben (BuP), and benzylparaben (BzP), which are often used as antimicrobial preservatives in food, pharmaceuticals, cosmetics, and personal care products (PCPs) [1]. The common alkylphenol derivatives 4-tert-butylphenol (4-t-BP) and 4-tert-octylphenol (4-t-OP) are ingredients in non-ionic surfactants, lubricants, and foaming agents and are, therefore, widely used in the production of soaps, cosmetics, paints, polycarbonate (PC), and insecticides [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, parabens have been found to disrupt the balance of thyroid hormones [20]. As for another common type of EDC, alkylphenols, several toxicological studies have shown that 4-t-BP and 4-t-OP can cause endocrine disruption and reproductive and developmental toxicity, and induce DNA damage and apoptosis in animals [3,[21][22][23][24]. Epidemiological studies have shown that exposure to 4-t-OP may increase the likelihood of male infertility [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation